Synthesis of Metal-Selenide Nanocrystals Using Selenium Dioxide as the Selenium Precursor - Chen, Ou; Chen, Xian; Yang, Yongan; Lynch, Jared; Wu, Huimeng; Zhuang, Jiaqi; Cao, Y. Charles (Angewandte Chemie (International ed.), 2008)
Quality and quantity: A non‐injection synthesis of high‐quality CdSe nanocrystals can be conducted in air, that is without the need for any oxygen‐free manipulation. The synthesis, which uses SeO2 as the selenium precursor, is suitable for the large‐scale industrial synthesis of high‐quality nanocrystals at low cost and has been generalized for the formation of other metal selenides, such as PbSe and Pd4.5Se nanocrystals.